Male Models. (Male Studio, 1962)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks
Redactie : International Male Studio, P.O. Box 330, Copenhagen V
Engels
Periodiek